Transdisciplinary pathways for wildlife conservation: A method for navigating socio‐ecological systems on private lands - Matthew Taylor; Aidan Davison; Andrew Harwood (People and Nature)
Abstract The decline of wildlife on private land is accelerating around the world. Resulting efforts to conserve wildlife on private lands are characterised by a complex socio‐ecological interplay between human practices and wildlife. Central to these socio‐ecological dynamics is the contradiction between fixed property boundaries and the mobility of wildlife, necessitating conservation strategies that transcend individual land parcels. Relevant human practices include land uses such as agriculture, forestry and housing, but also underlying economic, political and cultural relationships involved in private property in land. We focus here on private land in capitalist market societies. We argue that addressing the social‐ecological complexity involved in wildlife conservation in the context of land ownership in market societies requires new strategies that, more effectively than existing approaches, foster collaboration across private boundaries at an ecologically relevant landscape scale. While transdisciplinary strategies have had some application in private land conservation, there is opportunity to extend and mainstream these approaches by integrating social science insights into private property relations with innovations in citizen science and community conservation. We argue that most wildlife conservation initiatives are yet to take full advantage of opportunities provided by the social contract underlying private land for landscape‐scale landholder collaboration. Drawing on participatory conservation projects pioneered in Tasmania, Australia, we describe ‘transdisciplinary pathways’: a methodology for navigating the social‐ecological complexities of seemingly intractable wildlife conservation problems, by integrating theoretical and applied science with local ecological knowledge. This transdisciplinary knowledge integration is grounded in relationship building between researchers, conservation professionals and neighbourhood clusters of landowners. The resulting cohesive and adaptive networks of actors create pathways for wildlife conservation that are specific to local contexts while contributing to broader scientific and social learning. Read the free Plain Language Summary for this article on the Journal blog.